IMPLEMENTATION OF TOTAL QUALITY MANAGEMENT ON CONSTRUCTION OF ASSYRIAN LIBRARY PROJECT - Alwan, H.H.; Ali, A.A. Mohammed; Mahmood, Y.N. (International Journal of Research -GRANTHAALAYAH, 2021)
The purpose of this research is to evaluate the work of construction of an Assyrian library affiliated with the University of Mosul, which was based on conditions and procedures for quality control on both the administration and the engineering aspects taking in consideration the stages of the projects during the construction. When applying the quality requirements to the project in terms of achievement and integration, it found that there was a delay in the time of site implementation, in addition to the fact that the actual data with presumed. As well as the lack of high-quality data on the machines used for construction by the company. In general, however, some criteria have yielded satisfactory results in terms of on-site work.